Pentingnya Pencatatan Keuangan Dan Pencantuman Label Halal Produk Pada Home Industry Abon Ikan Tuna Segar G&R Masohi Shop Di Kelurahan Lesane Kecamatan Kota Masohi Kabupaten Maluku Tengah - Dwi Hariyanti; Wa Asrida; Sri Astuti Musaid; Tri Retno Hariyati (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
This community service was performed at the home industry of G&R Masohi Shope in Lesane Village, Masohi City District, Central Maluku Regency. This devotional activity is carried out with the aim to: 1) provide understanding and assistance to partners